Incidence and Associated Factors of Failed First Peripheral Intravenous Catheters among Adult Patients at Medical Surgical Wards in Public Referral Hospitals of West Amhara, Ethiopia, 2021 - Chanyalew Worku Kassahun; Addisu Taye Abate; Zewdu Baye Tezera; Debrewok Tesgera Beshah; Chilot Desta Agegnehu; Mehmmed Adem Getnet; Hailemichael Kindie Abate; Birhaneslasie Gebeyehu Yazew; Mahlet Temesgen Alemu (Hindawi Limited, 2022)
Background. Complications of peripheral intravenous catheters cause problems in clinical practice and bring high costs in terms of morbidity and mortality of patients. Therefore, this study aimed to assess the incidence and associated factors of failed first peripheral intravenous catheters among adult patients in selected Public Referral Hospitals of West Amhara Regional State, Ethiopia, 2021. Materials and Methods. An institution-based prospective observational study was conducted among 423 adult patients from January to February 2021. Patients were selected using systematic random sampling techniques. The data were collected using interviewer-based, structured questionnaires and observational checklists. EPI-DATA 3.1 and SPSS version-23 were used for data entry and analysis, respectively. Frequency, percentages, and means were calculated. The outcome variable was determined and graded based on phlebitis and infiltration scales. Binary and multivariable logistics regressions were computed. Results. Four hundred and seventeen first peripheral cannula sites from 418 patients were followed for 2,565 peripheral catheter hours. A failed first peripheral intravenous catheter was observed in 124 (29.7%, CI: 25.6-34) adult patients. Patients who were female (AOR = 0.4, 95% CI: 0.22-0.74) had cannula duration of 49-72 hours (AOR = 0.31, 95% CI: 0.14-0.7) and 73-96 hours (AOR = 0.39, 95% CI: 0.17-0.9), and patients who had been given electrolytes (AOR = 0.31, 95% CI: 0.11-0.86) were more likely to have failed first peripheral intravenous cannula. Conclusions. Failed first peripheral intravenous cannula is much higher as compared to the acceptable rate of ≤5% by the Infusion Nurses Society. Hence, all patients with peripheral intravenous catheters are screened for catheter failure at least once a day. Providing appropriate nursing care and patient education is also required to reduce the risks.